CEBPA mutational analysis in acute myeloid leukaemia by a laboratory-developed next-generation sequencing assay. Issue 6 (27th November 2017) - Ng, Christopher Wai Siong; Kosmo, Bustamin; Lee, Peak-Ling; Lee, Chun Kiat; Guo, Jingxue; Chen, Zhaojin; Chiu, Lily; Lee, Hong Kai; Ho, Sherry; Zhou, Jianbiao; Lin, Mingxuan; Tan, Karen M L; et al.
Abstract : Aim: The presence of biallelic CEBPA mutations is a favourable prognostic feature in acute myeloid leukaemia (AML). CEBPA mutations are currently identified through conventional capillary sequencing (CCS). With the increasing adoption of next-generation sequencing (NGS) platforms, challenges with regard to amplification efficiency of CEBPA due to the high GC content may be encountered, potentially resulting in suboptimal coverage. Here, the performance of an amplicon-based NGS method using a laboratory-developed CEBPA -specific Nextera XT (CEBNX) was evaluated. Methods: Mutational analyses of the CEBPA gene of 137 AML bone marrow or peripheral blood retrospective specimens were performed by the amplification of the CEBPA gene using the Expand Long Range dNTPack and the amplicons processed by CCS and NGS. CEBPA -specific libraries were then constructed using the Nextera XT V.2 kit. All FASTQ files were then processed with the MiSeq Reporter V.2.6.2.3 using the PCR Amplicon workflow via the customised CEBPA -specific manifest file. The variant calling format files were analysed using the Illumina Variant Studio V.2.2. Results: A coverage per base of 3631X to 28184X was achieved. 22 samples (16.1%) were found to contain CEBPA mutations, with variant allele frequencies (VAF) ranging from 3.8% to 58.2%. Taking CCS as the 'gold standard', sensitivity and specificity of 97% and 97% was achieved. For the transactivation domain 2 polymorphism (c.584_589dupACCCGC/p.His195_Pro196dup), the CEBNX achieved 100% sensitivity and 100% specificity relative to CCS. Conclusions: Our laboratory-developed CEBNX workflow shows high coverage and thus overcomes the challenges associated with amplification efficiency and low coverage of CEBPA. Therefore, our assay is suitable for deployment in the clinical laboratory.